APLIKASI AKTIVATOR UNTUK MEROMBAK ECENG GONDOK (Eichhornia crassipes (Mart.) Solms.) DARI DANAU TOBA MENJADI PUPUK ORGANIK - Juliani Juliani; Afifuddin Dalimunthe; Budi Utomo (Program studi Kehutanan USU, 2016)
Organic fertilizers such as compost is a natural fertilizer to add nutrients in the soil.Compost can be regarded as the product of fermentation of organic materials with a large number of microbes.The addition of activators or inoculum on the composting is part of an effort to accelerate the composting process. This research was done in November 2015 until January 2016 in experimental garden land USU campus in Padang Bulan, Medan. The experiment used a factorial randomized complete block design (RAK) factorial consisting of two factors.The first factor is the type of organic material consists of two levels the water hyacinth (Eichornia grassipes (Mart.) Solms.) smooth (A1) and the water hyacinth (Eichornia grassipes (Mart.) Solms.) rough (A2) and the second factor is the source of an organic activator which consists of four level without the type of activator (control) (B0), Mol fruit with vegetables (B1), Tape, tempe, with yakult (B2), and EM4 (B3). The parameters observed were comparison of temperature, pH and C/N ratio.The results of research showed that of water hyacinth (Eichornia grassipes (Mart.) Solms.) on some kind of local microorganisms (MOL) as fruit with vegetables (B1) MOL, Tape, tempe, with yakult (B2) MOL, and EM4 (B3) MOL, gives good the results of temperature, pH and C/N ratio of compost. Key words : Organic fertilizers, activators, the temperature of pH, the ratio of C/N.